Thermal conversion of aviation oils - E. A. Shaporova; S. V. Vasilevich; S. O. Stoiko; V. V. Shchur (Научный вестник МГТУ ГА)
These days, strict requirements to aeronautical equipment are imposed to enhance reliability, durability, and environmental compatibility. Aeronautical equipment operation reliability depends not only on its structural and technologic abilities, but also on the fact how aviation oils, fuels and technical fluid meet quality requirements during operation. During the aircraft engine operation, oils are subjected to the thermal impact. As a consequence, their properties and composition change which can affect the engine operation, on the whole. The most promising means of improving thermal resistance of aviation oils is developing new ones and improving available oil compositions. Therefore, it is feasible to analyze the kinetic properties of the oil thermal conversion which will make it possible to predict their resistance within the extensive temperature range. The paper investigates thermal decomposition kinetics of aviation oils MS-8P, TN-98 and TN-600 used on different types of aircraft in civil aviation of the Republic of Belarus by the method of a thermo-gravimetric analysis. The composition of oil samples has been researched into by IR spectroscopy, chromatography-mass spectroscopy methods. A comparative analysis of research results of new oils and oils drained from aircraft engines indicates that even under insignificant overheat during the operation, a change in the hydrocarbon composition occurs, and the hydrocarbon content of basic types varies to some extent. The oil thermolysis research reveals that potential overheat after engine shutdown complies with the temperatures at which the decomposition commences. Thermal conversion products of oil carbohydrates will contribute to the defect formation in friction subunits. As a result of test data processing of thermal conversion of aviation oils MS-8P, TN-98, TN-600, the principles of their decomposition as well as macrokinetic parameters, allowing us to precisely evaluate the effect of oils operation temperature conditions on their conversion rate, have been specified. It is essential while simulating the aircraft engine operation and predicting variations of oil quality properties during their operation.